Transition metal oxide and graphene nanocomposites for high-performance electrochemical capacitors - Zhang, Weifeng; Liu, Fu; Li, Qianqian; Shou, Qingliang; Cheng, Jipeng; Zhang, Li; Nelson, Bradley J.; Zhang, Xiaobin (Physical chemistry chemical physics : PCCP, 2012)
A method for producing nanocomposites of transition metal oxides A(3)O(4) (where A represents Mn, Fe or Co) and graphene nanosheets (GNS) is presented. The reduction of graphene oxide (GO) and the formation of A(3)O(4) nanoparticles (NPs) were carried out simultaneously during the reaction. The electrochemical properties of A(3)O(4)-GNS nanocomposites as electrode materials for supercapacitors are investigated by cyclic voltammetry and galvanostatic charge-discharge tests. The as-prepared Mn(3)O(4)-GNS, Fe(3)O(4)-GNS and Co(3)O(4)-GNS nanocomposites exhibit large specific capacitance (708, 358 and 240 F g(-1), respectively), high energy density (20, 10 and 7 W h kg(-1), respectively) and good electrochemical stability (retention of 73%, 67.8% and 95.8%, respectively, after 1000 charge-discharge cycles). The excellent electrochemical performance of the A(3)O(4)-graphene nanocomposites indicates great potential in the application in commercial supercapacitors.